2014
DOI: 10.7150/ijms.6540
|View full text |Cite
|
Sign up to set email alerts
|

Neural Cell Apoptosis Induced by Microwave Exposure Through Mitochondria-dependent Caspase-3 Pathway

Abstract: To determine whether microwave (MW) radiation induces neural cell apoptosis, differentiated PC12 cells and Wistar rats were exposed to 2.856GHz for 5min and 15min, respectively, at an average power density of 30 mW/cm2. JC-1 and TUNEL staining detected significant apoptotic events, such as the loss of mitochondria membrane potential and DNA fragmentation, respectively. Transmission electron microscopy and Hoechst staining were used to observe chromatin ultrastructure and apoptotic body formation. Annexin V-FIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…An increased in caspase-3 protein contents of a tissue is a sign of increased cellular apoptosis [27]. We have shown that GM-1 treatment has more significantly decreased the protein levels of caspase-3 in the spinal cord injured by bupivacaine in intrathecal GM-1s group than intravenous GM-1s.…”
Section: Groupmentioning
confidence: 97%
“…An increased in caspase-3 protein contents of a tissue is a sign of increased cellular apoptosis [27]. We have shown that GM-1 treatment has more significantly decreased the protein levels of caspase-3 in the spinal cord injured by bupivacaine in intrathecal GM-1s group than intravenous GM-1s.…”
Section: Groupmentioning
confidence: 97%
“…Therefore, they investigated the release of cytochrome C, the expression of Bax and Bcl-2, and caspase-3 activity in PC12 cells following MW radiation exposure. The study results showed that MWR exposure leads to increased Bax and reduced Bcl-2 and also caused the release of cytochrome c and the activation of caspase-3 (Rieger et al, 2011;Zuo et al, 2014).…”
Section: Evaluation Of Cell Death and Pathwaysmentioning
confidence: 96%
“…The primary energy producers in cells are mitochondria, and it has been reported by Zuo et al (2014) that mitochondrial dysfunction in neural cells occurred following microwave exposure. They analysed the quantity of early and late apoptosis in Annexin V (a Ca 2+ dependent phospholipid-binding protein), by using flow cytometry.…”
Section: Evaluation Of Cell Death and Pathwaysmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, the biological effects of electromagnetic waves and their impact on human health are of major concern (Jing et al 2012;Zuo et al 2014). Numerous epidemiological surveys…”
Section: Introductionmentioning
confidence: 99%